Fighting for Justice and Dignity: The Homer Seguin Story: An Autobiography - Seguin, Homer (Journal Printing, 2008)
Self-published memoir of the Sudbury union activist, Homer Seguin (1934-2013), who championed workplace health and safety to reduce injuries and occupational diseases at mines and other industrial sites. Describes his experiences as a negotiator, president of Local 6500 of the United Steelworkers, and as a USW representative at Elliot Lake, Ontario. Also chronicles the rise of the labour movement in Sudbury and the bitter inter-union battle in the early 1960s between Mine Mill Local 598 and the Steelworkers over the right to represent 20,000 Inco workers.
Keywords: 20th century; Elliot Lake; History. Industrial relations; History. Trade-unions; International Union of Mine; Mill and Smelter Workers. Local 598; Miners; Northeastern Ontario; Occupational health and safety; Seguin; Homer; Sudbury; United Steelworkers of America. Local 6500